The effect of cold rolling and high-temperature gas nitriding on austenite phase formation in AISI 430 SS - Kartika, Ika; Kurnia, Kevin; Senopati, Galih; Triwardono, Joko; Hermanto, Bambang; Rokhmanto, Fendy; Dwijaya, Made Subekti; Alfirano, Alfirano (Eastern-European Journal of Enterprise Technologies, 2021)
Austenitic stainless steel is the most commonly used material in the production of orthopedic prostheses. In this study, AISI 430 SS (0.12 wt. % C; 1 wt. % Si; 1 wt. % Mn; 18 wt. % Cr; 0.04 wt. % P and 0.03 wt. % S) will be modified by creating austenite and removing its ferromagnetic properties via the high-temperature gas nitriding process. Cold rolling with various percentage reduction (30, 50, and 70 %) was followed by gas nitriding at a temperature of 1200 °C with holding times of 5, 7, and 9 hours, then quenching in water was carried out on as-annealed AISI 430 SS. The formation of the austenite phase was examined by XRD (x-ray diffraction). The microstructure and element dispersion were observed using SEM-EDS (scanning electron microscope-energy dispersive spectrometry), whereas the mechanical properties after gas nitriding and water quenching were determined by Vickers microhardness testing. At all stages of the gas nitriding process, the FCC iron indicated the austenite phase was visible on the alloy’s surface, although the ferrite phase is still present. The intensity of austenite formation is produced by cold rolling 70 % reduction with a 5-hour gas nitriding time. Furthermore, the nitrogen layer was formed with a maximum thickness layer of approximately 3.14 µm after a 50 % reduction in cold rolling and 9 hours of gas nitriding process followed by water quenching. The hardness reached 600 HVN in this condition. This is due to the distribution of carbon that is concentrated on the surface. As the percent reduction in the cold rolling process increases, the strength of AISI 430 SS after gas nitriding can increase, causing an increase in the number of dislocations. The highest tensile strength and hardness of AISI 430 SS of 669 MPa and 271.83 HVN were obtained with a reduction of 70 %.